Pengelolaan Harta Wakaf Produktif Di LNW Ibadurrahman Duri Kabupaten Bengkalis untuk Kesejahteraan Ummat - Mukhlis Mukhlis (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2019)
Management of productive endowments is part of the economic efforts of development and utilization to create goodness in the life of the Islamic community, the results of endowments obtained from the endowment will be distributed for the benefit of the people. The management of productive waqf assets in LNW Ibadurrahaman Duri has established public welfare programs that aim to improve lives and alleviate the poverty of the Islamic Ummah.